Examining the Causes and Consequences of Wrongful Arrests in Law Enforcement: Menelaah Penyebab dan Konsekuensi Salah Tangkap dalam Penegakan Hukum - Yunita, Aingga Rahma; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Wrongful arrests represent a significant issue within the criminal justice system, garnering public attention due to their serious consequences. Specific Background: These errors can stem from various factors, including eyewitness misidentification, insufficient evidence, and systemic pressures on law enforcement. Knowledge Gap: Despite the known implications of wrongful arrests, there remains a lack of comprehensive understanding regarding the psychological and social impacts on victims, as well as effective preventive measures. Aims: This research aims to explore the underlying causes of wrongful arrests, their effects on individuals and society, and to identify actionable steps for mitigation. Results: Utilizing qualitative methods, including in-depth interviews and case studies with victims, law enforcement officials, and legal experts, the study reveals that the primary contributors to wrongful arrests are errors in eyewitness identification and the urgency to close cases. Victims report severe psychological trauma and enduring social stigma alongside material losses. Novelty: The findings highlight the necessity of integrating advanced technology in identification processes and revising existing policies to reduce wrongful arrests. Implications: The research underscores the importance of enhanced training for law enforcement, the ethical use of technology, and the establishment of compensation mechanisms for victims, advocating for systematic reforms to strengthen public trust in the justice system and promote accountability in law enforcement practices. Highlights: Causes: Eyewitness errors and inadequate evidence lead to wrongful arrests. Impact: Victims experience trauma and social stigma from wrongful arrests. Recommendations: Improve training and use advanced technology for identification. Keywords: wrongful arrest, eyewitness identification, psychological impact, law enforcement, policy reform